Growth peculiarities of Weddell seal pups (Leptonychotes weddellii) - I. V. Dykyy; O. O. Salganskiy (Ukrainian Antarctic Journal, 2013)
The peculiarities of growth of Weddell seal youngs (Leptonychotes weddellii) on the material collected during 11th, 14th, 16th Ukrainian Antarctic expeditions (2006-2007, 2009-2010, 2011-2012) within the territory of the Argentine Islands (West Antarctica) was investigated. According to the monitoring of L. weddelli pups the relatively large body size (131–140 cm) and weight (18–25 kg) were found compare to literature data. This can indicate the sufficient food supply for the pregnant females of the species in the waters of the archipelago. It was found that daily gain of pups is 3.6 kg on average. The highest absolute and average daily gains of the pups during nine day term was from 5 to 7 kg. This shows a strategy of the highest liveweight gain during the first week after birth that can be explained as the adaptation for another feeding schedule. It was found that the majority of pups up to 21 days of age are gaining more than 90 kg of weight. This enables them to move on to the water way of life, to dive and to maintain low water temperatures. It was noted that the initial terms of birth of Weddell seal youngs within the archipelago differ in time (ranging from late August to late September) and probably depend on the peculiarities of weather conditions during the spring season. The research of growth intensity dynamics of Weddell seal youngs enables us to evaluate and determine the quality of forage reserve in the region of Archipelago of Argentine Islands.